2012
DOI: 10.1007/s00246-012-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Heart Rate and Cardiac Dysfunction in Duchenne Muscular Dystrophy

Abstract: Sinus tachycardia is common in cases of Duchenne muscular dystrophy (DMD). The authors hypothesized that an elevated heart rate would herald cardiomyopathy onset. A retrospective case-control study was performed with 55 DMD boys and 150 age-matched control boys. The variables were age, heart rate, shortening fraction, and left ventricular end-diastolic dimension. Cardiomyopathy was defined as a shortening fraction less than 28%. The DMD boys had a higher initial heart rate with no baseline echocardiographic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 26 publications
4
45
2
5
Order By: Relevance
“…For the calculation of the energy expenditure, the heart rates and the gait V ave were considered. In accordance with the literature 19 , the RHR of the evaluated patients was higher than in the healthy group studied by Rose et al 1 . This result may be explained by the autonomic nervous system dysfunction, which occurs precociously in patients with DMD, causing decreased parasympathetic activity and/or increased sympathetic activity with the progression of the disease 20 .…”
Section: Discussionsupporting
confidence: 92%
“…For the calculation of the energy expenditure, the heart rates and the gait V ave were considered. In accordance with the literature 19 , the RHR of the evaluated patients was higher than in the healthy group studied by Rose et al 1 . This result may be explained by the autonomic nervous system dysfunction, which occurs precociously in patients with DMD, causing decreased parasympathetic activity and/or increased sympathetic activity with the progression of the disease 20 .…”
Section: Discussionsupporting
confidence: 92%
“…The average heart rate at enrollment and the reduction of average heart rate correlated with a positive change in EF. 124 Thomas et al 229 initially showed that boys with DMD with normal LV function but with elevated heart rate were more likely to progress to cardiomyopathy than those in the lower quartiles for heart rate. This was followed by the finding that autonomic dysfunction before the onset of HF was associated with myocardial fibrosis, which suggests a role for earlier treatment.…”
Section: β-Adrenergic Blockadementioning
confidence: 99%
“…An elevated resting heart rate (HR) is frequently observed early in the natural history of DMD associated cardiac disease [5,19], prior to the onset of changes in ejection fraction (EF), and this elevated resting HR may be a form of abnormal heart rate variability (HRV) implicating autonomic dysfunction. HRV has been used in multiple diseases as a measure of cardiac autonomic activity and has been associated with various morbidity and mortality outcomes in acute myocardial infarction [1,2,20], congenital heart disease [10], diabetic neuropathy [15], congestive heart failure, [4,17] and amyotrophic lateral sclerosis [16] but limited data are available evaluating HRV variables in DMD patients.…”
Section: Introductionmentioning
confidence: 99%